Controversies in implementing non‐invasive prenatal testing in a public antenatal care program - Kjell Åsmund Blix Salvesen; Ragnhild Glad; Vasilis Sitras (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Women's autonomy and an inclusive society for all individuals are highly valued in Norway. The Norwegian Biotechnology Act changed in 2020 allowing first‐trimester screening and cell‐free DNA for common trisomies to all pregnant women. However, implementing non‐invasive prenatal testing (NIPT) in a public antenatal care program is difficult, because many patients, politicians, and medical professionals do not consider trisomy 21 a severe medical disease. Screening for trisomies at an early gestation might inevitably lead to an increase in pregnancy terminations and making cost–benefit calculations is ethically challenging. Moreover, offering NIPT to all pregnant women is debatable because of the lower prevalence of fetal trisomies in younger women. Therefore, appropriate genetic pre‐test counseling is essential. Furthermore, organizing the service between private institutions and public hospitals poses another debate and challenges both quality and equal access to health services for women across the country.